2022
DOI: 10.3390/molecules27165073
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Hepatic and Intestinal Integrity by Phyllanthus amarus Is Dependent on Bax/Caspase 3 Modulation in Intestinal Ischemia-/Reperfusion-Induced Injury

Abstract: Ethnopharmacological relevance: Oxidative stress is a key player in intestinal ischemia/reperfusion (I/R) injury (IIRI) with a tendency to trigger systemic inflammatory response, resulting in progressive distal organ injury. To date, the role of Bax/caspase 3 signaling in IIRI has not been reported. Furthermore, the discovery of a safe and effective drug remains pertinent in improving the outcome of IIRI. Therefore, this study investigated the role of Bax/caspase 3 signaling in intestinal I/R-induced intestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 84 publications
0
10
0
1
Order By: Relevance
“…All of these studies required the use of one animal per sampling incident, which highlights the importance of techniques that optimise the use of experimental animals. [20][21][22][23][24][25][26][27][28][29] In our selective clamping IIRI-BK model, we obtained five samples from the same injured intestine, considerably reducing the number of rats and allowing kinetic studies. In addition, SI morphological damage and villus recovery were comparable with several previous results published by our group and others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of these studies required the use of one animal per sampling incident, which highlights the importance of techniques that optimise the use of experimental animals. [20][21][22][23][24][25][26][27][28][29] In our selective clamping IIRI-BK model, we obtained five samples from the same injured intestine, considerably reducing the number of rats and allowing kinetic studies. In addition, SI morphological damage and villus recovery were comparable with several previous results published by our group and others.…”
Section: Discussionmentioning
confidence: 99%
“…Among experimental studies focused on gastrointestinal diseases found in the literature, IIRI-and 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced colitis in rats appears as a current model used by many authors and research groups around the world. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] For this reason, we selected these two relevant pathologies to evaluate the experimental BK procedure in an intestinal injury scenario. IIRI was used for simulating a model of intestinal intussusception, strangulated hernia or intestinal transplantation.…”
Section: Step 2 Bk Model Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals were prepared for surgical induction as earlier stated ( 35 , 36 ). The rats were weighed and anesthetized with 10 mg/kg of Xylazine and 50 mg/kg of Ketamine.…”
Section: Methodsmentioning
confidence: 99%
“…De los estudios experimentales focalizados en patología de intestino delgado la IIR es un modelo de interés en la actualidad. (91)(92)(93)(94)(95)(96)(97)(98)(99)(100) Materiales y métodos: Se emplearon ratas Wistar hembras (peso 221 ± 13 gr). A las mismas se les proporcionó agua y alimento a demanda previo al acto quirúrgico.…”
Section: Bk Para El Estudio De La Iir Intestinalunclassified